2001
DOI: 10.1002/bies.1073
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol: a neglected variable in metabolic processes?

Abstract: Glycerol is a small and simple molecule produced in the breakdown of glucose, proteins, pyruvate, triacylglycerols and other glycerolipid, as well as release from dietary fats. An increasing number of observations show that glycerol is probably involved in a surprising variety of physiopathologic mechanisms. Glycerol has long been known to play fundamental roles in several vital physiological processes, in prokaryotes and eukaryotes, and is an important intermediate of energy metabolism. Despite some differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
125
0
13

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(143 citation statements)
references
References 60 publications
1
125
0
13
Order By: Relevance
“…16 It is well known that nearly 60% of synthesized glycerol is metabolized to glycerol-3-phosphate, which is one of the key metabolic intermediates for ATP production. 32 Hara-Chikuma et al found that glycerol supplementation corrected the reduced proliferation and ATP content in AQP3 deficiency, with cellular glycerol, ATP and enhanced chemiluminescence (ECL) detection system following manufacturer's instructions and visualized by autoradiography with Hyperfilm. RNA interference (RNAi) experiments.…”
Section: Discussionmentioning
confidence: 99%
“…16 It is well known that nearly 60% of synthesized glycerol is metabolized to glycerol-3-phosphate, which is one of the key metabolic intermediates for ATP production. 32 Hara-Chikuma et al found that glycerol supplementation corrected the reduced proliferation and ATP content in AQP3 deficiency, with cellular glycerol, ATP and enhanced chemiluminescence (ECL) detection system following manufacturer's instructions and visualized by autoradiography with Hyperfilm. RNA interference (RNAi) experiments.…”
Section: Discussionmentioning
confidence: 99%
“…It is an important intermediary in energy metabolism and a substrate for the biosynthesis of various lipids 6) . In addition, glycerol can control osmotic activity in the cytoplasm 6) .…”
Section: Discussionmentioning
confidence: 99%
“…It is an important intermediary in energy metabolism and a substrate for the biosynthesis of various lipids 6) . In addition, glycerol can control osmotic activity in the cytoplasm 6) . A recent study on expression of AQP3 in skin has shown that AQP3-facilitated water transport is involved in cell migration and accelerating wound healing; furthermore, AQP3-facilitated glycerol transport is involved in generating ATP and facilitates epithelial cell proliferation and differentiation, and also tumorigenesis 13,15,16,38) .…”
Section: Discussionmentioning
confidence: 99%
“…There can be several alternative glycerol dissimilation pathways, including the NADP-linked glycerol dehydrogenase route and the FAD-linked Gly-3-P dehydrogenase route (42). It has been suggested according to its phylogenetic distribution that glycerol metabolism can be taken back as far as the prebiotic era (43). It was recently demonstrated that glycerol supplied exogenously to extracellular hyphae of the symbiotic mycorrhiza is incorporated into triacylglycerol in the intracellular hyphae, and subsequently transferred to the extracellular hyphae as an energy source (44).…”
Section: Discussionmentioning
confidence: 99%